Pornography Issues and Its Distribution in Twitter (Immoral Similar Artist Video Case) - Christiany Juditha (Jurnal Penelitian Komunikasi dan Opini Publik, 2021)
For two decades, the spread of pornography on the internet has been difficult to contain. The Ministry of Communication and Information has blocked 1,062,558 pornographic content during January-September 2020 which is generally circulating on social media. The case of the spread of immoral videos who look like an artist that went viral has shown the fact that the spread of pornography is at an alarming stage. Therefore, the aim of this research is to get a picture of the spread of pornographic issues (immoral videos similar to artists) on Twitter. This research method uses the Social Media Analysis method with the Brand24 application. The results of the study concluded that this video was first uploaded on Twitter and began to be discussed on November 5, 2020. The highest peak of this issue was discussed the next day with the reach graph which increased sharply. The spread within days was massive and out of control. Even though this video was deleted by the first uploader, it has already been circulated, spread, saved and then shared again through other social media platforms. The spread is even more viral because it is accompanied by a special hashtag in every tweet. The results of data crawling concluded that the sites most active in spreading this issue were Twitter.com, Youtube.com and Tribunnews.com. This video also spreads to other media such as blogs, forums and instant messaging applications, Telegram. The characteristics of social media which are networks and sharing facilities allow the spread of this issue to be more viral and massive in various media.